Raw biomass electroreforming coupled to green hydrogen generation - Hu Zhao (Nature Portfolio, 2021)
The scale-up of the coupling of water electroreduction (HER) with organic electrooxidation remains challenging. Here the authors address this challenge by coupling HER with electrooxidation of raw biomass chitin, cogenerating acetate and green hydrogen safely at high current density.